Efektivitas Pelaksanaan Vaksin Polio dalam Meningkatkan Kesadaran Masyarakat Desa Sialang indah Terhadap Pentingnya Imunisasi di Desa Sialang Indah Kecamatan Pangkalan Kuras, Kabupaten Pelalawan - Asep Saefullah; Alya Tri Tasya Nurmaini; Abdimas Khodijaya; Alfiyanti Khusnunnisa; Gita Putri Sinaga; Raja Anissa; Sinta Ramadani; Syarah Marlina; Tika Oktavia; Yemima V Perangin angin; Mujiono Mujiono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Real Work Lecture (KKN) is a form of community service activity by students with a cross-scientific and sectoral approach at a certain time and area. The implementation of KKN activities usually lasts between one to two months and takes place in villagelevel areas. The Directorate General of Higher Education in Indonesia has requires every university to carry out KKN as an intracurricular activity that combines the tri dharma of higher education, namely: education, research, and community service. We observed how the effectiveness of polio vaccine implementation in increasing community awareness of the importance of immunization in Sialang Indah Village, Pangkalan Kuras Sub-district, Pelalawan Regency. The virus will damage the nervous system of the sufferer's body so that there can be a risk of paralysis, difficulty breathing, or even death. The polio virus often affects toddlers or children under 5 years old, especially if they have not had the polio vaccination. However, it is not impossible that polio can also be experienced by adults.